Scaphoid Fracture Reconstruction with Rib Autograft: Case Report and Literature Review - Fomkinas, Mantas; Kievišas, Mantas; Braziulis, Kęstutis; Rimdeika, Rytis (Lietuvos chirurgija, 2021)
Objective. To evaluate the results of scaphoid bone proximal pole reconstruction with rib osteochondral autograft due to comminuted scaphoid fracture. Material and methods. We present a clinical case of fragmented scaphoid bone proximal pole fracture reconstruction by rib osteochondral autograft. The modified wrist function score of Green and O’Brien and Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) outcome measuring scales were used for clinical evaluation before and 6 months after the reconstruction. Additionally, a literature review was conducted for case reports and previous literature reviews describing scaphoid bone proximal pole fracture surgical treatment. Medline (PubMed), ScienceDirect and UpToDate databases were used. Results. Conventional treatment methods for the treatment of comminuted proximal pole scaphoid bone fractures are often inappropriate due to technical issues or potential adverse outcomes. In these cases, reconstruction with rib autograft is possible. The study patient’s modified wrist function score of Green and O’Brien increased from 75 to 95 points out of 100 at 6 months postoperatively, and the Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) score decreased from 13.64 to 4.55 points. The results of this technique have been investigated in several studies (Sandow, 1998, 2001; Veitch et al., 2007). All subjects (22, 47 and 14 patients, respectively), except one, experienced improvement of wrist function – enhanced wrist movement, grip strength, reduced pain and restored wrist function to the pre-injury performance level. Conclusions. Scaphoid bone proximal pole fragmented fracture reconstruction with osteochondrial rib autograft achieves favorable recovery of wrist function and avoids complications or unfavorable functional consequences of alternative surgical procedures.